Ciudad y medio ambiente - Cuadrat Prats, José María; De la Riva Fernández, Juan; López Martín, Fernando; Martí Ezpeleta, Alberto (Geographicalia, 2017)
This work shows the first results of the empirical analysis about the heat island in Teruel city. Firstly, morphological and functional characteristics of the urban area described. Next the collected data in the urban itineraries are analysed, and the existente of a moderate heat island is verified, with 2,2º C ofmaximum intensity with a long design around two sectors, the historical centre and the Ensanche (urban development).
Keywords: Environment; urban climate; heat island; Teruel